A study on franchisee protection under the franchising regulation in China - Xinbo, Huang (2025)
Since the early 1990s, franchising in China has experienced rapid growth, but concerns about misuse and fraud have been raised among regulators. This study examines the legal and regulatory framework governing the franchising sector to evaluate whether the current framework adequately protects franchisees. The objectives are to: (1) study the current franchising regulation in China, (2) analyse the existing protection for franchisees in China, (3) examine the practices of franchisee protection with specific reference to the United States, Australia and Malaysia, and (4) propose recommendations for improving the franchising regulation for a better protection of franchisees. This study adopts a doctrinal legal approach, supplemented by qualitative interviews with 21 respondents, including potential franchisees, franchisees, franchisors, lawyers and regulators. Data collected through library research and interviews are analysed using content analysis, thematic and critical methods. The findings indicate that the current franchising regulation protects franchisees' interests through mandatory disclosure, post-registration requirements and contractual mechanisms. However, interview findings reveal that the current regulatory framework offers limited protection for franchisees, with unclear disclosure, weak enforcement of registration and imbalanced contracts. A critical analysis of regulatory practices in the United States, Australia and Malaysia highlights the need for clearer disclosure, stronger enforcement of registration and fairer contractual safeguards to better protect franchisees. This study recommends clarifying disclosure requirements, strengthening registration and enhancing contractual safeguards to create a fairer franchising environment.